Dexter. Resurrection. The complete first season [videorecording (DVD)] - Irwin, Pat, 1955- (Showtime Networks, 2026)
"Weeks after the harrowing events of Dexter: New Blood, Dexter Morgan awakens from a coma to discover that his son, Harrison, is missing. Determined to find him and make things right, Dexter sets out for New York City. But when Miami Metro's Angel Batista arrives with questions, Dexter realizes his past is catching up to him fast. As father and son navigate their own darkness, they soon find themselves deeper than they ever imagined."--